The Development of a Preliminary Design for a Tidal Energy Plant - Samo, K. A.; Baharun, A.; Rigit, A. R. H. (Engineering, Technology & Applied Science Research, 2021)
Renewable energy sources are considered a part of the future of energy production in Malaysia. The main objectives of this research are to append a new energy extraction technique that harvests energy from tides and to develop a preliminary design for a tidal energy plant at Kuching Barrage. Knowing the diameter of the turbine, the dimensions of the powerhouse are achieved in conjunction with site conditions. The centerline should be at least below the low water tide so that the tide is at all times guaranteed to be submerged. Based on this, the powerhouse has a 24.61m length, is about 100m in distance across, and its elevation is 36.39m. The construction is located downstream and the centerline habitation at -1.15 and below LSD. The calculated tidal energy plant is comprised of four bulb-type turbines installed at each barrage gate. The bulb-type turbine blades would face the sea site with 11.32m length of the draft tube. This study detailed feasibility study can be implemented.